Rifampin enhances cytochrome P450 (CYP) 2B6-mediated efavirenz 8-hydroxylation in healthy volunteers - Cho, Doo-Yeoun; Shen, Joan H.Q.; Lemler, Suzanne M.; Skaar, Todd C.; Li, Lang; Blievernicht, Julia; Zanger, Ulrich M.; Kim, Kwon-Bok; Shin, Jae-Gook; Flockhart, David A.; Desta, Zeruesenay (Drug metabolism and pharmacokinetics, 2016)
The effect of rifampin on the in vivo metabolism of the antiretroviral drug efavirenz was evaluated in healthy volunteers. In a cross-over placebo control trial, healthy subjects (n = 20) were administered a single 600 mg oral dose of efavirenz after pretreatment with placebo or rifampin (600 mg/day for 10 days). Plasma and urine concentrations of efavirenz, 8-hydroxyefavirenz and 8,14-dihydroxyefavirenz were measured by LC–MS/MS. Compared to placebo treatment, rifampin increased the oral clearance (by ∼2.5-fold) and decreased maximum plasma concentration (Cmax) and area under the plasma concentration–time curve (AUC0–∞) of efavirenz (by ∼1.6- and ∼2.5-fold respectively) (p < 0.001). Rifampin treatment substantially increased the Cmax and AUC0–12h of 8-hydroxyefavirenz and 8,14-dihydroxyefavirenz, metabolic ratio (AUC0–72h of metabolites to AUC0–72h efavirenz) and the amount of metabolites excreted in urine (Ae0–12hr) (all, p < 0.01). Female subjects had longer elimination half-life (1.6–2.2-fold) and larger weight-adjusted distribution volume (1.6–1.9-fold) of efavirenz than male subjects (p < 0.05) in placebo and rifampin treated groups respectively. In conclusion, rifampin enhances CYP2B6-mediated efavirenz 8-hydroxylation in vivo. The metabolism of a single oral dose of efavirenz may be a suitable in vivo marker of CYP2B6 activity to evaluate induction drug interactions involving this enzyme. [Display omitted]